Intervenciones urbanas para cohesión social de los asentamientos informales del municipio de Yumbo (2024)
The research aims to analyze urban and architectural design strategies to promote social cohesion in informal neighborhoods of Yumbo, Valle del Cauca, focusing on the "Las Palmas" sector. The housing issue in Yumbo originates from the lack of affordable housing and high industrial activity, resulting in high density, lack of public space, and infrastructure deficiencies.